Performance of H-ZSM-5/TiO2 Nanocatalyst on Green Biodiesel Synthesis from Tobacco Seed Oil (Voor-Oogst and Na-Oogst) as Renewable Energy - Sri Wahyuni; Sri Rahmawati; Muhammad Rusdi; M. Ikhwan Najmi; Irving Dahlan Saksak (Lambung Mangkurat University Press, 2026)
Based on the seasons in Indonesia, tobacco is classified into two types: cigar tobacco (Na-Oogst) and cigarette or kretek tobacco (Voor-Oogst). Tobacco seeds contain around 36-41% oil, which has the potential to be a renewable energy source. Biodiesel is one of the renewable alternative energy sources that has received much attention because it is a clean and green energy. Biodiesel is produced from triglycerides through a transesterification reaction with homogeneous and heterogeneous catalysts. Heterogeneous catalysts are more attractive because they can be regenerated and are environmentally friendly. The advantages of this catalyst are that it has good catalytic activity due to its large surface area and superior stability. Zeolite H-ZSM-5 appears as a solid acid catalyst with a promising microporous structure for esterification and transesterification reactions. In this study, TiO2 doping was added to improve the performance of the H-ZSM-5 catalyst. TiO2 is a leading photocatalyst because it has chemical, biological, and non-toxic stability. Furthermore, to determine the success of the synthesis of H-ZSM-5/TiO2 as a nanocatalyst, XRD, FTIR, SEM-EDX Mapping characterization was carried out. The results showed that the addition of TiO2 which has a particle size distribution of 46.07 nm in the synthesis of H-ZSM-5/TiO2 did not cause changes in structure and degree of crystallinity. The experimental parameters of transesterification that were varied were catalyst concentration. The results of the transesterification reaction yielded the highest methyl ester of 87.5% at optimum reaction conditions and a catalyst concentration of 2% w/w with a molar ratio of oil and methanol (1:12). The synthesized methyl ester has a characterization value that enters the range of SNI biodiesel values, so that the synthesized methyl ester has the potential to be used as biodiesel. We hope that this research can inspire researchers related to heterogeneous nanocatalyst research that is more efficient and rational and has good stability in the production of sustainable renewable fuels.